2015
DOI: 10.11113/jt.v74.3183
|View full text |Cite
|
Sign up to set email alerts
|

Steady State Load Shedding to Prevent Blackout in the Power System using Artificial Bee Colony Algorithm

Abstract: Real and reactive power deficiencies due to generation and overload contingencies in a power system may decline the system frequency and the system voltage. During these contingencies cascaded failures may occur which will lead to complete blackout of certain parts of the power system. Under such situations load shedding is considered as an emergency control action that is necessary to prevent a blackout in the power system by relieving overload in some parts of the system. The aim of this paper is to minimize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Figure 10 shows an observation of the line active and reactive power losses before, during the overload contingency, and after load shedding. When compared to the losses recorded by [6], this approach records lower losses, which is in line of minimizing system losses and load to be shed. From the figure, a total Power generated (MW) Figure 7: Losses versus generated power.…”
Section: Overload Contingenciesmentioning
confidence: 96%
See 2 more Smart Citations
“…Figure 10 shows an observation of the line active and reactive power losses before, during the overload contingency, and after load shedding. When compared to the losses recorded by [6], this approach records lower losses, which is in line of minimizing system losses and load to be shed. From the figure, a total Power generated (MW) Figure 7: Losses versus generated power.…”
Section: Overload Contingenciesmentioning
confidence: 96%
“…Undervoltage Load Shedding (UVLS) and Underfrequency Load Shedding (UFLS) are the criteria mainly used for load shedding [5]. rough the shedding of some loads, the perturbed system is forced to settle to a new state of equilibrium [6]. However, for any method of load shedding to be successful, the amount to be shed should be optimal, at the correct location and be done on the right time so as to prevent any possibility of voltage instability and also avoid losing the customer trust in the utility company [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…42,43 Voltage collapse is a major challenge for power system operators. [44][45][46][47] Factors such as changing nature loads, dependency on generation remotely positioned away from load centers, and natural load growth increase the risk of voltage collapse. 41,48 The risk of voltage instability further rises because of heavily overburdened power networks and jams during failures and outages.…”
Section: Voltage Collapsementioning
confidence: 99%
“…An ABC algorithm proposed in [ 18 ] showed that higher power transfer to heavily loaded buses was achieved as compared to conventional methods, namely projected augmented Lagrangian method (PALM) and the gradient-technique based on Kuhn-Tucker theorem (GTBKTT). However, the voltage operation conditions achieved ranged from 0.95 to 1.17 p.u., falling outside the required range for voltage stability to be maintained.…”
Section: Introductionmentioning
confidence: 99%